PENGARUH CURRENT RATIO, RETURN ON EQUITY DAN EARNING PER SHARE TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2010 – 2019 - Susi Lusiana (JURNAL ILMIAH EDUNOMIKA, 2021)
The study of this research is to determine the effect of returning shares in manufacturing companies. This study uses the financial ratios contained in the company's financial statements. The financial ratios used in this study are the current ratio, return on equity, and earnings per share to stock returns in manufacturing companies listed on the Indonesian stock exchange in 2010-2019. This type of research used in this research is quantitative and the analytical method used is purposive sampling using SPSS 21 as many 10 manufacturing companies in the food, beverage, textile, rubber goods (tires), fisheries, and agriculture sectors. Data collection techniques are used by retrieving data through the website www.idx.co.id. The results showed that Current Ratio (CR) has a positive and significant effect on Stock Returns, Return On Equity (ROE) has a positive and significant effect on Stock Returns, and Earning Per Share (EPS) has a negative and significant effect on Stock Return.